Russia’s war in Ukraine: A world order under transformation? - Flockhart, Trine (Politica, 2023)
The article outlines processes of order transformation in light of Russia’s war in Ukraine. The article argues that transformation is taking place at three levels of ordering conceptualized as the global order level, the international order level, and the national order level. The article shows that transformation is currently taking place at all three levels: in the ideational foundations of the global rules-based order; in the number of ordering entities at the international order level as the Russian-led Eurasian order and the Chinese-led Belt-and-Road order consolidate; and at the national order level through the emergence of right-wing populism. The article demonstrates the importance of paying attention to all three levels, and that Putin’s ambition for a viable Eurasian order probably is unlikely to be met, but that this is not necessarily cause for optimism about the coming world order.